Uso do hidrogel no cultivo de Peperomia obtusifolia em substratos submetidos a diferentes capacidades de retenção de água - Rodrigues, Pablo Eanes Cocco (2023)
The efficiency of water use is increasingly necessary, in view of its demand for the production of ornamental plants in substrates. Understanding the factors involved in water consumption is essential for quality production with low environmental impact. In this context, the use of hydrogel as a soil/substrate conditioner enables the gradual absorption and availability of water to plants, which may increase the efficiency of water and nutrient use in cultivation in containers and in a protected environment. Thus, the objectives of this work were to identify and quantify the influence of hydrogel doses and substrate moisture levels on the productive variables of Peperomia obtusifolia grown in a protected environment, and to measure the response of different polymer doses on the substrate drying curve. The experiment was carried out at the Federal University of Santa Maria, in 2021 and early 2022. Four doses of hydrogel (0, 20, 40 and 60 g.L-1) and four percentages of the water retention capacity in the pot (25, 50, 75 and 100%CRV). The design used was completely randomized, with three replications for each treatment. According to the analysis of the substrate, significant effects of the doses on the physical and chemical attributes were found. In the drying curve, the highest dose of hydrogel was able to store water for a longer time when compared to the control and the lowest dose of polymer. The control (without hydrogel) presented the highest values for the parameters plant height and number of leaves and root length. The peperomia plants were more responsive to the different %CRV than to the evaluated hydrogel doses. Therefore, the hydrogel can be an alternative for areas with water scarcity, since the highest dose of hydrogel resulted in the highest plant heights for the lowest CRV. Thus, the hydrogel is not indicated for the cultivation of peperomia, since the control proved to be superior to all evaluated doses.